Compósitos de polietileno de ultra-alto peso molecular (PEUAPM) e quasicristal (AlCuFe): comportamento térmico e mecânico. - Figueiredo, Lucas Ricardo Fernandes (2013)
The preparation of composite polymers with fillers and / or fibers has been a way of obtaining new materials and improvement of polymeric materials performance. In this scenario, loads of metallic quasicrystals AlCuFe have been emerged with high potential for use as reinforcement in polymer composites due their properties such as high hardness, friction and wear. In addition, quasicrystal loads can act as potential electrical insulators and they are excellent conductors of heat. This work presents a study of the thermal and mechanical behavior of composites made of Polyethylene ultra high molecular weight polyethylene (UHMWPE) and quasicrystal (AlCuFe). These composites were characterized by differential scanning calorimetry (DSC), thermogravimetry (TG), tensile testing, flexural testing, fracture toughness, and scanning electron microscopy (SEM). The DSC analyses suggest that with addition loads of quasicrystals into the matrix, the degree of crystallinity is increased. In TG analyses, the addition of the loads did not change the thermal stability of matrix, and mass losses remained in a single step. The mechanical tensile testing showed a slight increase of elastic modulus with increasing load, whereas for the bending testing an increase of elastic modulus occurred until to 2% load. The analysis of SEM showed a lack of load/matrix adhesion, and a good distribution of quasicrystal in UHMWPE composites. The fracture energy was decreased when the load of quasicrystal was increased in UHMWPE composites, resulting in a more fragile behavior of 98/2, 95/5 and 90/10 composites than pure UHMWPE.